2007
DOI: 10.1038/sj.bjc.6603963
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of matrix metalloproteinases and their inhibitors in mononuclear inflammatory cells in breast cancer correlates with metastasis-relapse

Abstract: An immunohistochemical study was performed using tissue microarrays and specific antibodies against matrix metalloproteinase (MMP)-1, -2, -7, -9, -11, -13 and -14, tissular inhibitors of metalloproteinase (TIMP)-1, -2 and -3. More than 2600 determinations on cancer specimens from 131 patients with primary ductal invasive tumours of the breast were performed. To identify specific groups of tumours with distinct expression profiles the data were analysed by unsupervised hierarchical cluster analysis by each cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
71
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(85 citation statements)
references
References 59 publications
13
71
1
Order By: Relevance
“…Endostatin can be cleaved from collagen XVIII by several proteinases, such as MMPs-3, -7, -9, -13, -14 and -20, elastase and cathepsin L (Seppinen and Pihlajaniemi, 2011). Both tumour cells and tumour-associated local inflammatory cells are able to produce several of these enzymes (Nielsen et al, 1996;Brabletz et al, 1999;Heljasvaara et al, 2005;González et al, 2007). In accordance with an earlier report (Li et al, 2012), we found a significant correlation between high serum endostatin concentration and poor tumour differentiation.…”
Section: Discussionsupporting
confidence: 81%
“…Endostatin can be cleaved from collagen XVIII by several proteinases, such as MMPs-3, -7, -9, -13, -14 and -20, elastase and cathepsin L (Seppinen and Pihlajaniemi, 2011). Both tumour cells and tumour-associated local inflammatory cells are able to produce several of these enzymes (Nielsen et al, 1996;Brabletz et al, 1999;Heljasvaara et al, 2005;González et al, 2007). In accordance with an earlier report (Li et al, 2012), we found a significant correlation between high serum endostatin concentration and poor tumour differentiation.…”
Section: Discussionsupporting
confidence: 81%
“…Thereby, multivariate analysis indicates that to belong to this cluster group is the most significant and independent prognostic factor to predict distant metastasis development in patients with IDC [132]. In addition, these two differential MICs phenotypes with distinct prognosis were also found in breast carcinomas with luminal A or in basal-like phenotype [133], which suggests the importance of the expression of MMPs/TIMPs by the stromal cells as prognostic factors independently of the signature of cancer cells.…”
Section: Mmps and Timps Expression In Micsmentioning
confidence: 88%
“…These associations are relevant because these highly expressed genes have been associated with several biological mechanisms related to tumor progression [151][152][153][154][155][156][157]. It is also relevant the novel finding of the association between the expression of MMP-11 or TIMP-2 by the MICs at the tumor center and a high CD68/(CD3+CD20) ratio (macrophages (CD68 [158], since both proteins are the two principal factors defining the prometastatic phenotype of MICs in our previous studies [34,132,134,144]. In addition, if there is a high CD68/(CD3+CD20) ratio at the invasive front, most of MICs with a positive MMP-11 or TIMP-2 phenotype at the tumor center are macrophages, suggesting all these findings that a high CD68/(CD3+CD20) ratio at the invasive front contributes to polarize macrophages to achieve a high metastatic phenotype at the tumor center.…”
Section: Mmps and Timps Expression In Metastasismentioning
confidence: 96%
See 2 more Smart Citations